Accuracy of two face-bow/semi-adjustable articulator systems in transferring the maxillary occlusal cant - Nazia Nazir; M Sujesh; Ravi Kumar; P Sreenivas (Wolters Kluwer Medknow Publications, 2012)
Context: The precision of an arbitrary face-bow in accurately transferring the orientation of the maxillary cast to the articulator has been questioned because the maxillary cast is mounted in relation to arbitrary measurements and anatomic landmarks that vary among individuals. Aim: This study was intended to evaluate the sagittal inclination of mounted maxillary casts on two semi-adjustable articulator/face-bow systems in comparison to the occlusal cant on lateral cephalograms. Materials and Methods: Maxillary casts were mounted on the Hanau and Girrbach semi-adjustable articulators following face-bow transfer with their respective face-bows. The sagittal inclination of these casts was measured in relation to the fixed horizontal reference plane using physical measurements. Occlusal cant was measured on lateral cephalograms. SPSS software (version 11.0, Chicago, IL, USA) was used for statistical analysis. Repeated measures analysis of variance and Tukey's tests were used to evaluate the results (P < 0.05). Results: Comparison of the occlusal cant on the articulators and cephalogram revealed statistically significant differences. Occlusal plane was steeper on Girrbach Artex articulator in comparison to the Hanau articulator. Conclusion: Within the limitations of this study, it was found that the sagittal inclination of the mounted maxillary cast achieved with Hanau articulator was closer to the cephalometric occlusal cant as compared to that of the Girrbach articulator. Among the two articulators and face-bow systems, the steepness of sagittal inclination was greater on Girrbach semi-adjustable articulator. Different face-bow/articulator systems could result in different orientation of the maxillary cast, resulting in variation in stability, cuspal inclines and cuspal heights.